Plant-strong : discover the world's healthiest diet--with 150 Engine 2 recipes - Esselstyn, Rip (Grand Central Life & Style, 2015)
"In this #1 New York Times bestseller (originally published as My Beef with Meat), Rip Esselstyn arms readers with the 36 most powerful facts that prove, once and for all, that a plant-based diet can save your life. Do you want to: Prevent cancer, heart attacks, stroke, and Type 2 Diabetes? Eat plants! Have stronger bones than milk could ever give you? Eat plants! Avoid dangerous carcinogens and contaminants? Eat plants! Lose weight and look great? Eat plants! On top of these arguments are 150 other reasons why plants rule--as in 150 delicious, mouth-watering Engine 2 recipes, including 10 that are exclusive to this new edition. Prepare to eat well, be healthy, and live plant-strong!,"--Amazon.com.